“University students’ economic situation during the COVID-19 pandemic: a cross-sectional study in Germany” - Gewalt, Sandra Claudia; Berger, Sarah; Krisam, Regina; Krisam, Johannes; Breuer, Markus (PLOS ONE, 2022)
The COVID-19 pandemic caused a major economic downturn that disproportionally affected university students. This empirical research investigated effects and risk factors of the pandemic on students’ economic situation with focus on financial distress and financial limitations. Data was collected using an online survey in May and June 2020 from students (n = 917) enrolled at universities in Germany. 80.6% were enrolled in bachelor programs (n = 738), the mean semester was 3.8 (standard deviation (SD = 2.0) and students’ mean age was 23.1 years (SD = 4.1). 51.8% (n = 472) were female and 47.4% (n = 432) male. 56.7% (n = 506) of students worked before the pandemic. More than one third reported a decrease in income (36.5%; n = 334) and an increase in financial constraints (38.7%; n = 354). A multivariate logistic regression analysis showed that students with regular income were less likely to experience financial distress compared to those without (odds ratio (OR) = 0.456; p = 0.014). Furthermore, working part-time as associated with a higher financial distress compared to those without part-time employment (OR = 1.811; p = 0.003). Students who worked part-time before the pandemic also had a higher probability of increased financial restriction (or constraint) compared to those who did not work part-time (OR = 2.094; p < 0.001). University students were disproportionally affected by the economic consequences of the COVID-19 pandemic, which increased students’ economic uncertainty. To offset such problems, financial aid schemes for students need to be made available to alleviate distress and to allow students to focus on their studies but should not compound problems by leading to financial hardship at a later point in time.
Gesehen am 16.01.2023